Purification of Sucrose in Sugar Beet Molasses by Utilizing Ceramic Nanofiltration and Ultrafiltration Membranes - Mikael Sjölin; Johan Thuvander; Ola Wallberg; Frank Lipnizki (Membranes, 2019)
Molasses is a sugar mill by-product with low value that today is used primarily for animal feed. However, molasses contains large amounts of sucrose which, if purified, could be used for other purposes. In this study, purification by membrane filtration using ceramic tubular ultrafiltration (UF) and nanofiltration (NF) was examined. NF purifies sucrose by removing small compounds, whereas UF removes larger compounds. Based on our results, high filtration fluxes could be obtained, and it was possible to clean the membranes sufficiently from fouling compounds. Sucrose was separated from other compounds, but the separation efficiency was generally higher with diluted molasses compared with concentrated molasses. This could be explained by more severe fouling when filtering dilute molasses or potentially due to aggregate formations in the molasses as our analysis showed. Overall, this study shows the potential of ceramic UF and NF membranes for sucrose purification from molasses.